Professional portrait of future instructors for physical education of preschool - T.M. Semanychyn; S.L. Popel’ (Physical Education of Students)
Purpose: identify the degree of readiness of students to conduct valeological activity in preschool educational institutions. The objective of the study was to identify the relationship between educational level and health education and readiness of students to valeological activities. Material : in the experiment took part 550 students. Results : the survey allowed to establish pedagogical assumptions that characterize the training of students. This will include valeological activity for the formation of their own culture valeological children. It is shown that students’ valeological culture is a prerequisite for the effective functioning of the system in pre-secondary institutions. It is noted that the training of students of the Faculty of Physical Education and Sports to valeological activity is low. Conclusions : studies have shown that only 11.7% of the students have been trained and have the necessary knowledge and practical skills.